Case Report: Uterine mesothelial cyst in a nulliparous woman—diagnostic and clinical challenges of a rare benign lesion - Shao, Ying; Liu, Yi; Yang, Chun (Frontiers in Medicine, 2025)
Uterine mesothelial cysts (UMCs) are rare, benign lesions that arise from the mesothelial lining of the uterus and are only sporadically documented in the literature. Because of their extremely low incidence, the clinical presentation and imaging features of UMCs are often nonspecific, which makes preoperative diagnosis particularly challenging. We report the case of a 46-year-old nulliparous woman who presented with an intramural cystic mass of the uterus. Preoperative imaging suggested a benign lesion, but the differential diagnosis included cystic degeneration of leiomyoma, adenomyotic cyst, and endometriosis. The patient underwent a laparoscopic cystectomy, during which the cyst was completely excised without intraoperative complications. She recovered uneventfully and was discharged on postoperative day three. Histopathological examination confirmed the diagnosis of a uterine mesothelial cyst. At 1 month of follow-up, no recurrence was observed. This case highlights the importance of surgical excision for both definitive diagnosis and treatment, emphasizes the challenges in preoperative assessment, and contributes valuable clinical evidence to the limited body of knowledge on UMCs.